EPID-01. SEX DIFFERENCE IN EXPRESSION OF IRON-RELATED GENES AND SURVIVAL IN GLIOBLASTOMA PATIENTS. (11th November 2019) - Lee, Sang; Walter, Vonn; Salzberg, Anna; Nesterova, Darya; Lathia, Justin; Rubin, Joshua; Berens, Michael; Barnholtz-Sloan, Jill; Connor, James
Abstract: Sex impacts the clinical outcome of glioblastoma (GBM) patients. Iron is a key metabolic driver in glioma biology impacting both the neoplastic cells directly and tumor progression through the immune system. We previously reported the expression of HFE (iron homeostatic) gene has a sexually dimorphic impact on survival in GBM patients. To further interrogate the relationship of iron and sexual dimorphism in GBMs, we expanded our analysis to include the ferrome (profile of genes and proteins involved in iron regulation). These genes were identified using IronChip and then interrogated for sexually dimorphic expression and survival in primary GBM patients using The Cancer Genome Atlas GBM database. Biological pathway analysis indicated that the Toll receptor signaling and immune system signaling pathways are most strongly correlated to sex difference and GBM patient survival. Toll like receptor 4 ( TLR4 ) expression in the bottom quartile is associated with a modest survival benefit for female GBM patients compared to male, but in the top quartile of expression of this gene the survival for males is dramatically greater than that for females (18 months versus 3.6 months). Males expressing top quartile of Dual specificity phosphatases ( DUSP1 ) also known as MKP1 survive 24.2 months whereas females survive 5.8 months. There is no sex effect of DUSP1 in the bottom quartile of expression. These data suggest that top quartile expression of TLR4/DUSP1 are both a benefit for males (extending their survival) and a detriment to females (shortening their survival). Both TLR4 and DUSP1 are richly expressed in macrophages. The data suggest that macrophage infiltration into the tumor could be particularly negatively impactful in females; a finding consistent with our previous reports for the HFE gene. In summary, iron related gene expression is linked to sexual dimorphism in survival and may provide insights on sex specific tumor biology.